Korea [videorecording] - The Travel Preview System (Houston, Tex. Travelview International, 1996)
Feature the sights and sounds of South Korea, the ancient kingdom.
Title on container: Korea : the beginning of a great vacation.
VHS.
Keywords: Korea (South) -- Description and travel